Sustainable Marketing within the Environmental Responsibility Context: Research and Communication Strategies for Businesses Growth - ZRYBNIEVA, IRYNA; Burdyak, Oleh; Venherova, Olena; Nosachenko, Oleksandr; Serhiienko, Oleksandr (Grassroots Journal of Natural Resources, 2025)
This article aims to investigate the role of marketing research and communication tools in developing sustainable marketing strategies to improve business efficiency in the context of environmental protection. The study's methodological approach is based on a combination of quantitative and qualitative analysis methods. In particular, qualitative methods include the synthesis of literary sources, systematization and generalization; while quantitative methods are based on the application of statistical analysis, in particular the calculation of the Sustainable Marketing Index (SMI). This approach allowed us to determine the level of integration of sustainable practices into the marketing strategies of European enterprises and to identify the relationship between the volume of investments and the financial capabilities of businesses to implement them. Additionally, we conducted an impact analysis of marketing research on strategic decision-making, cost optimization and increasing the profitability of enterprises. As a result of the calculations, it was established that most companies recognize the feasibility of investing in sustainable marketing campaigns (ІСМ𝑠𝑚𝑎𝑙𝑙 = 1,75; ІСМ𝑚𝑒𝑑𝑖𝑢𝑚 = 2,259; ІСМ𝑙𝑎𝑟𝑔𝑒 = 1,99), which is confirmed by the growth of budgets and allotted time resources for their implementation. It was determined that the level of investment in sustainable development depends on the scale of the company, macroeconomic factors and the effective communication with stakeholders. The study confirmed that the level of investment in sustainable marketing campaigns increases depending on the scale of the company and macroeconomic conditions, and as stated, effective interaction with stakeholders seemed to be a determining factor in the success of such strategies.
Keywords: Marketing research; Communication tools; Sustainable marketing; Sustainable development; Environment; Environmental marketing